About the Usage and Usability of Central Venous Catheters in Children with TPN: the Parents’ Viewpoint - Tüshaus, Ludger; Kelly, Kathrin; Siebert, Julia; Kohl-Sobania, Martina (Klinische Pädiatrie, 2023)
Background Medical devices are important components of medical care. Therefore, they must be safe and useful for patients. This study aimed to analyze the situation of children with central venous catheters (CVCs) for long-term parenteral nutrition from the parents’ perspective with respect to patient safety and usefulness.Methods An online cross-sectional survey was conducted using a quantitative research approach, with a German patient support group for children with chronic intestinal failure.Results 61 responses were collected between November 202 and January 2021. Concerning the usability of the CVCs, the caregivers assessed overall satisfaction, patient safety, usability, learnability of handling, “self-explanatory ability, “ and mental load. Furthermore, various suggestions for improvements have been documented.Conclusion Although CVCs can cause a variety of complications in the context of long-term use, the usage for parents in everyday life is feasible. Insufficient fixation and protection outside of the body have been identified as unmet clinical needs. In addition to the underlying disease of chronic intestinal failure, the catheter adds an extra mental burden to families’ lives. Furthermore, parents articulated the need for further information and training.
Keywords: chronic intestinal failure; central venous catheter; medical device; usability; short bowel syndrome; child